Cover Feature: Cysteine‐Rich Peptides: Hyperstable Scaffolds for Protein Engineering (6/2021). (3rd March 2021) - González‐Castro, Rafael; Gómez‐Lim, Miguel A.; Plisson, Fabien
Abstract : Cysteine‐rich peptides are being used as stable scaffolds to produce bioactive grafted peptides with either a single epitope (first generation), two identical epitopes (second generation), or two distinct epitopes (third generation). The spatial grid is a metaphor for the tridimensional design one needs to consider when combining a scaffold with one or more epitopes. More information can be found in the minireview by F. Plisson et al. Picture by R. G.‐C.